Synthesis and conformational analysis of fluorinated pyrrolidines - Combettes, L; Lorraine Combettes (2012)
The aim of this thesis was to investigate the synthesis and the conformational analysis of fluorinated pyrrolidines. We focused on two strategies namely, the iodoamination and fluoroamination of fluorinated precursors. Iodoamination Our first approach for the synthesis of fluorinated pyrrolidines relied on the iodocyclisation of allylic fluorides bearing pendant nitrogen nucleophiles. These allylic fluorides were obtained by fluorodesilylation of suitably functionalised allylsilanes. After validation of this methodology, the scope and limitations of the iodoamination were investigated. Furthermore, we were able to probe the influence of the fluorine moiety on the level of diastereocontrol of the cyclisation. Fluoroamination The second route focused on a key reaction: an unprecedented electrophilic fluoroamination of an aminated allylsilane. From a mechanistic point of view, the presence of the silyl group act as a 1,2-dipole and activate the double bond towards electrophilic fluorination. This methodology required the initial screening of a silyl directing group that would promote electrophilic addition, without subsequent desilylation. Finally, we investigated the level of diastereocontrol displayed by these cyclisations as a function of the E/Z geometry of the starting aminated allylsilane. Conformational analysis Moreover the 3-fluoropyrrolidines obtained via iodoamination served to investigate the stereoelectronic influence of the fluorine gauche effect on ring conformations. Solid state single crystal X-ray analysis and solution phase NMR spectroscopy were used for this purpose. Due to complicated conformational analysis of saturated five-membered rings in solution, 1D 19F-1H heteronuclear nOe (HOESY) experiments have been optimised for applications to this type of small molecules. These have been employed to estimate 19F-1H internuclear distances and were combined with vicinal 3JFH and 3JHH scalar coupling constants in order to analyse the ring conformations.